Long‐term oncological and functional follow‐up in low‐dose‐rate brachytherapy for prostate cancer: results from the prospective nationwide Swiss registry. (12th February 2020) - Viktorin‐Baier, Pascal; Putora, Paul M.; Schmid, Hans‐Peter; Plasswilm, Ludwig; Schwab, Christoph; Thoeni, Armin; Hochreiter, Werner; Prikler, Ladislav; Suter, Stefan; Stucki, Patrick; Müntener, Michael; Blick, Nadja; et al.
Abstract : Objective: To evaluate the long‐term oncological, functional and toxicity outcomes of low‐dose‐rate brachytherapy (LDR‐BT) in relation to risk factors and radiation dose in a prospective multicentre cohort. Patients and Methods: Data of patients from 12 Swiss centres undergoing LDR‐BT from September 2004 to March 2018 were prospectively collected. Patients with a follow‐up of ≥3 months were analysed. Functional and oncological outcomes were assessed at 6 weeks, 6 and 12 months after implantation and annually thereafter. LDR‐BT was performed with 125 I seeds. Dosimetry was done 6 weeks after implantation based on the European Society for Radiotherapy and Oncology recommendations. The Kaplan–Meier method was used for biochemical recurrence‐free survival (BRFS). A prostate‐specific antigen (PSA) rise above the PSA nadir + 2 was defined as biochemical failure. Functional outcomes were assessed by urodynamic measurement parameters and questionnaires. Results: Of 1580 patients in the database, 1291 (81.7%) were evaluable for therapy outcome. The median (range) follow‐up was 37.1 (3.0–141.6) months. Better BRFS was found for Gleason score ≤3+4 ( P = 0.03, log‐rank test) and initial PSA level of <10 ng/mL ( P < 0.001). D'Amico Risk groups were significantly associated with BRFS ( P < 0.001), with a hazard ratio of 2.38 for intermediate‐ and high‐risk patients vs low‐risk patients. The radiation dose covering 90% of the prostate volume (D90) after 6 weeks was significantly lower in patients with recurrence. Functional outcomes returned close to baseline levels after 2–3 years. A major limitation of these findings is a substantial loss to follow‐up. Conclusion: Our results are in line with other studies showing that LDR‐BT is associated with good oncological outcomes together with good functional results.